Characterisation of Pseudomonas mosselii H6 for aerobic denitrification: stoichiometry and reaction kinetics - Tian Hu; Jiating Wei; Yihang Ding; Shuo Li; Weicheng Zhang; Jun Zhang (Biotechnology & Biotechnological Equipment)
The application of aerobic denitrifying bacteria in biological nitrogen removal has been of great interest. However, the mechanism of nitrogen conversion by aerobic denitrifying bacteria is unclear due to the lack of stoichiometry and kinetic studies. Therefore, this study aimed to investigate the stoichiometry and kinetics of aerobic denitrification using Pseudomonas mosselii H6 as a model strain. The results showed that the stoichiometric equations of strain H6 under different nitrogen source conditions were obtained by nitrogen balance analysis; the concentrations of different limiting substrates were set and combined with the multi-substrate Monod kinetic equation to fit the half-saturation constants of COD, ammonia, nitrate and nitrite nitrogen for strain H6, which were 230.1008, 25.3435, 4.1009 and 23.4601 mg/L, respectively; based on the model of “two-step denitrification”, the numerical simulation of the growth and aerobic denitrification of strain H6 under different limiting substrate concentrations was carried out by using AQUASIM software to test the validity of stoichiometric coefficients and kinetic constants and perfect fitting results were obtained. These parameters will help to simulate the growth and denitrification performance of aerobic denitrifying bacteria and provide an experimental basis for further quantitatively elucidating the mechanism of action in the aerobic denitrification process.